Penentuan Faktor-Faktor Bahaya yang Dihadapi Perawat di RSUD Kabupaten Karanganyar dan Usulan Pencegahannya Menggunakan Metode AHP - Irwan Iftadi; Wakhid Ahmad Jauhari; Agarika Fatmasari (Performa: Media Ilmiah Teknik Industri, 2011)
From the calculation of weighting the results of biological hazard 0.23 0.22 followed by a chemical hazard and environmental and mechanical biomechanical hazard 0.22, 0.17 and hazard pshycal 0.17 pshychological hazard. While the determination of the value of performance, the lowest hazard of pshychological hazard to the value 3.991 4.113 followed by a biological hazard, chemical hazard 4.309, environmental and mechanical / biomechanical hazard and the highest 4.396 4.578 pshycal hazard. Proposed hazard prevention based on the lowest of pshychological hazard with hazard specification, among others, due to the many patients, patients who want immediate demands are met, the threat from the patient and the supervisor, invective from the patient and the supervisor, shift changing, the staff were not adequate and heavy workloads. From the results of questionnaires and interviews with the nurse, the things that need to be considered is the quantity of hospital nurses, nurses and quality of work on the hospital system.